Europe during the energy crisis - Klaus-Heinrich Standke (Intereconomics, 1974)
Shortages of fuels and raw materials had been pre dicted for the world not before the turn of the century, and even experts were surprised that a situation of general undersupply arrived so soon. As there is little scope for substitution, and the currency system of the world is in peril, industrialised nations have only a narrow field for remedial action. In the long term, there may be some hope, however, for breaking out of the dilemma with the aid of a new technology.
Keywords: 330; Energy Problems